(untitled) (Sains Humanika, 2016)
Fashion is the popular or the latest style of clothing or behaviour that evolves with time. Fashion may influence the way of living of the society. The current fashion scene presents to the general public an abundance of fashion trends. However, most of them tend to accentuate the figure of the wearer which does not meet the concept of covering aurah properly, with designs that are see-through or close-fitting. This matter must be taken into consideration since covering the aurah is compulsory in the Islamic Law. This article, therefore, discusses women fashion according to the Islamic perspective and its impact on their physical and spiritual health. From the physical aspect, dressing according to the Islamic way can balance the stimulation of the hormone and mind.Â In addition to regulating the body temperature through the head, it coordinates the balance between a healthy body and good brain functioning. It also aids in the development of a great intellect and motivation, and it encourages the development of positive behaviour. Meanwhile, from the spiritual aspect, it deepens their faith and piety to Allah, as well as gives high confidence and self-esteem in the women. It also preserves their dignity and honour. Hence, the fundamentals of the fashion design that is based on the Islamic way of dressing are beneficial in attaining the blessings from Allah and maintaining a good health.